Interconnection of Educational and Professional Standards - D. V. Dementev (Учёт. Анализ. Аудит)
The paper discusses some issues of existing norms and requirements to educational and professional activities. The required soft (non-technical), general professional and professional skills are prescribed by educational standards, job descriptions are regulated by professional standards. Higher education programs must provide quality professional skills. A mandatory assessment and monitoring of professional skills should become a powerful motivator for employees’ long-life learning and selfeducation. A criterion for assessing the quality of education is a graduate who works in the specialty and qualitatively fulfils the job responsibilities. The reference to the statistics in educational and budgeting spheres is used to raise the problem of practical compliance of educational standards and professional job functions. Educationalstandardsshouldspecifythejobsappropriateforthegraduate.The control over competence formation must ensure the qualitative qualification. The conclusion is made that an employer does not finds it beneficial to retrain a certified specialist. A graduate of higher educational institution should be able to immediately fulfill the duties stated in his job description. In all stages of their higher education program, students should learn by doing to enhance skills by action learning, which must be ensured by the educational institution. In this regard, internship curriculum should be constantly monitored and regularly updated. There is an urgent need for educators to take up part-time jobs with relevant non-educational organizations or to receive regular refresher training. As for engaging outside professionals from non-educational organizations, it could be considered only as exception. It is proposed to develop a separate educational standard for the training of lecturers of higher education, as teachers must master the methodology of teaching students. A standard to guide professional activities of lecturers should also be worked out and recommended for practical application. This standard should be an extension of the educational standard. The potential and viability of this study is proved by the draft educational standards that put educational skills in compliance with professional standards (job descriptions).The growing number of publications on harmonizing educational and professional standards is also an evidence of its topicality.